Association between mental health and executive dysfunction and the moderating effect of urban–rural subpopulation in general adolescents from Shangrao, China: a population-based cross-sectional study. Issue 8 (23rd August 2022) - Lin, Qingmin; Abbey, Cody; Zhang, Yunting; Wang, Guanghai; Lu, Jinkui; Dill, Sarah-Eve; Jiang, Qi; Singh, M K; She, Xinshu; Wang, Huan; Rozelle, Scott; Jiang, Fan
Abstract : Objectives: To examine the association between mental health and executive dysfunction in general adolescents, and to identify whether home residence and school location would moderate that association. Design: A population-based cross-sectional study. Setting: A subsample of the Shanghai Children's Health, Education, and Lifestyle Evaluation-Adolescents project. 16 sampled schools in Shangrao city located in downstream Yangtze River in southeast China (December 2018). Participants: 1895 adolescents (48.8% male) which were divided into three subpopulations: (A) adolescents who have urban hukou (ie, household registration in China) and attend urban schools (UU, n=292); (B) adolescents who have rural hukou and attend urban schools (RU, n=819) and (C) adolescents who have rural hukou and attend rural schools (RR, n=784). Measures: The Depression Anxiety and Stress Scale-21 was used to assess adolescent mental health symptoms, and the Behaviour Rating Inventory of Executive Function (parent form) was applied to measure adolescent executive dysfunction in nature setting. Results: Mental health symptoms were common (depression: 25.2%, anxiety: 53.0%, stress: 19.7%) in our sample, and the prevalence rates were lower among UU adolescents than those among the RR and RU, with intersubgroup differences in screen exposure time explaining most of the variance. We found the three types of symptoms were strongly associated with executive dysfunction in general adolescents. We also observed a marginal moderating effect of urban–rural subgroup on the associations: UU adolescents with depression (OR 6.74, 95% CI 3.75 to 12.12) and anxiety (OR 5.56, 95% CI 1.86 to 16.66) had a higher executive dysfunction risk when compared with RR youths with depression (OR 1.93, 95% CI 0.91 to 4.12) and anxiety (OR 1.80, 95% CI 1.39 to 2.33), respectively. Conclusions: Rural adolescents experienced more mental health symptoms, whereas urban individuals with mental health problems had a higher executive dysfunction risk.